A New View of Long-Term Geomagnetic Field Secular Variation - Lund, Steve P. (Frontiers in Earth Science, 2018)
This study carries out a statistical analysis of high-resolution PSV records for the last ~70 ka from three different regions of the Earth. We consider directional and intensity variability in each region on time scales of 103-105 years in order to evaluate long-term PSV. We then compare those results with more traditional long-term PSV statistical studies averaged over ~106 years. Three replicate PSV records from one region (subtropical North Atlantic Ocean) were averaged at overlapping 3ka and 9 ka intervals. Variability in both scalar inclination and declination variability and vector angular dispersion are significant and coherent among the three records. The vector dispersion is relatively low for most of the time but contains two relatively narrow intervals (~30-42 ka and 60-65 ka) of high dispersion. (Vector dispersion in all records was calculated after removing directions with true excursional VGPs, VGPs < 45° N.) We have carried out a comparable statistical analysis on two other PSV records from other parts of the Earth (Chile margin; Philippines/Indonesia). The results for these three regions are comparable in their overall style of variability. The scalar directional variability from the Philippines/Indonesia is quite different in detail from the other two regions, as might be expected, but the scalar directional variability between the Western Hemisphere regions is remarkably consistent considering their distance from one another. This may be associated with them being on the same longitude swath and having some coherent dynamo activity occurring along that path. Three magnetic field excursions occur in the study interval. All three excursions are associated with the two highest vector dispersion intervals. Paleointensity records from the three regions were subjected to the same statistical analysis as the directions. These records are allso coherent in their pattern of variability. The similarity in paleointensity variability on a global scale is expected even though the detailed scalar directional variability is not coherent on a global scale. The pattern of intensity variability is strongly correlated with the pattern of vector dispersion and excursions on a global scale – high (low) intensity is associated with low (high plus excursions) vector dispersion.